Awareness of intratumoral bacteria and their potential application in cancer treatment - Yin Liang; Qiyan Li; Yulin Liu; Yajie Guo; Qingjiao Li (Discover Oncology, 2023)
Abstract Hitherto, the recognition of the microbiota role in tumorigenesis and clinical studies mostly focused on the intestinal flora. In contrast to the gut microbiome, microorganisms resident in tumor tissue are in close contact with cancer cells and therefore have the potential to have similar or even different functional patterns to the gut flora. Some investigations have shown intratumoral bacteria, which might come from commensal microbiota in mucosal areas including the gastrointestinal tract and oral cavity, or from nearby normal tissues. The existence, origin, and interactions of intratumoral bacteria with the tumor microenvironment all contribute to intratumoral microorganism heterogeneity. Intratumoral bacteria have a significant role in tumor formation. They can contribute to cancer at the genetic level by secreting poisons that directly damage DNA and also intimately related to immune system response at the systemic level. Intratumoral bacteria have an impact on chemotherapy and immunotherapy in cancer. Importantly, various properties of bacteria such as targeting and ease of modification make them powerful candidates for precision therapy, and combining microbial therapies with other therapies is expected to improve the effectiveness of cancer treatment. In this review, we mainly described the heterogeneity and potential sources of intratumoral bacteria, overviewed the important mechanisms by which they were involved in tumor progression, and summarized their potential value in oncology therapy. At last, we highlight the problems of research in this field, and look forward to a new wave of studies using the various applications of intratumoral microorganisms in cancer therapy.